ON THE SYSTEM OF DECENTRALIZATION TO LOCAL GOVERNMENT - พระวิสุทธวรกิจ (Journal of MCU Phetchaburi Review, 2021)
The decentralization of government in Thailand has evolved. Continuously since the reign of King Chulalongkorn has developed up to the present, occurred in the era after the change of government in 1932, that is, local government in Thailand began in the reign of King Chulalongkorn, which has undergone major bureaucratic reforms, with the establishment of the first Bangkok sanitation. Later, with the establishment of a sanitary Chalom. And the Sanitation Districts are a lot more. Later, in the reign of King Prajadhipok, a committee was assigned to R.D. CRAIG, Government Foreign Adviser Serves to prepare a draft municipal law Make sure the municipality has a governing body More self-sanitation models Who are often given to the Minister, the Governor or a regional government official as a supervisor by the municipal law body Has been prepared but Not promulgated until the government revolution in 1932, the decentralization committee for the local government organization should play a role in determining which is a complex mission. Between the state and the local government organization or between the local government organization together Along with measures to support decentralization And divided missions Appropriate responsibility between the central and regional and local With a focus on development according to the guidelines of good governance at the international level The prosperity of population leads to the development and change according to the world conditions, so various development systems implemented and developed. To be appropriate and able to make society coexist with equality and to strengthen to occur in the culture of the people ever since